2019
DOI: 10.1002/ejlt.201900201
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of n‐3 Polyunsaturated Phosphatidylglycerol from Salmon Roe Lipids by Phospholipase D and In Vitro Digestion

Abstract: Phosphatidylglycerol (PG) is a highly functional phospholipid (PL), which has many physiological functions. However, naturally occurring PG binding n‐3 polyunsaturated fatty acid (n‐3 PUFA) is low in content, resulting in a scarcity of industrial bio‐resources of n‐3 PUFA enriched PG. The current study investigates the preparation of salmon roe PG (SRPG) from three types of salmon roe lipids and glycerol via phospholipase D (PLD)‐mediated transphosphatidylation. The yields of SRPG obtained from salmon roe tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…We repeated the PLD-catalyzed transphosphatidylation to prepare sufficient amounts of n-3 PUFA-PG for the animal experiment. The purity of the n-3 PUFA-PG was greater than 95% (Supplemental Figure S1), as confirmed by high performance chromatography as described in our previous paper [13].…”
Section: Preparation Of N-3 Pufa-pgsupporting
confidence: 78%
See 2 more Smart Citations
“…We repeated the PLD-catalyzed transphosphatidylation to prepare sufficient amounts of n-3 PUFA-PG for the animal experiment. The purity of the n-3 PUFA-PG was greater than 95% (Supplemental Figure S1), as confirmed by high performance chromatography as described in our previous paper [13].…”
Section: Preparation Of N-3 Pufa-pgsupporting
confidence: 78%
“…The crude PLs were obtained by the acetone precipitation of salmon roe lipids, as in a previous study [13]. The obtained insoluble precipitate (crude PLs) of 4.5 g was dissolved in 200 mL ethyl acetate and mixed with 200 mL of 0.2 M sodium acetate buffer (pH 5.6) containing 10 mM CaCl 2 ; then, 75 g glycerol was added.…”
Section: Preparation Of N-3 Pufa-pgmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 31 ] Recent studies have shown that phospholipases C and D play an important role in the hydrolysis of PL. [ 32,33 ] This study found that phospholipase C and PLD have higher activity during storage, as shown in Figure 4. Studies have shown that phospholipase C and PLD catalyze TAG to produce FFA and PUFA.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, it has been used for the preparation of plasmid-DNA lipid and polymeric nanovaccines showing that anionic PLs could increase antigen delivery, transport, and stability [75]. Unfortunately, PG could be recovered only in small amounts from natural sources and, even if it has been prepared by different groups [76][77][78], the possibility to set-up new strategies of synthesis is mandatory especially for the biomedical investigations.…”
Section: Preparation Of Phosphatidylglycerolmentioning
confidence: 99%